Myanmar's Agriculture Sector: Unlocking the Potential for Inclusive Growth - David A. Raitzer; Larry C. Y. Wong; Jindra Nuella G. Samson (Asian Development Bank (ADB), 2015)
Myanmar's agriculture sector offers substantial unexploited potential to underpin the country's inclusive economic development. With extensive land, water, and labor resources, as well as proximity to fast-growing markets, the country's agriculture has key competitive advantages. At the same time, Myanmar's agricultural productivity trails its neighbors as a result of constraints in input markets, infrastructure, and institutions. Key actions to address these constraints include improving land tenure, expanding credit availability, investing in input markets for nutrients and machinery, developing drainage and irrigation systems, and enhancing rural transport and electricity connectivity. In the shortterm, public-private partnerships may help to address these barriers to investment, but increased public investment is vital over the longer term. All these direct actions should be underpinned by investments in innovation and attention to climate change effects as part of comprehensive long-term agricultural development planning.
hdl:11540/5300
Keywords: O13; Q13; Q15; Q18; 330; agricultural policy; crop performance; fisheries and aquaculture; input markets development; Myanmar